ANALISIS PROSESI TRADISI KIRAB PUSAKA SATU SURA ISTANA MANGKUNEGARAN SURAKARTA - Pradipta, Made Prasta (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to find out the procession of Kirab Pusaka Satu Sura at Mangkunegaran Palace Surakarta, and the constrains of the Satu Sura Mangkunegaran Palace Surakarta procession. The object of this research is Mangkunegaran Palace Surakarta. The type of research used in this research is qualitative. The data in this study were collect using observation, interviews, and documentatiton. The population in this study were the organizers of the kirab and the courtiers of the Mangkunegaran Palace Surakarta with a total of five person. The data analysis technique used is data reduction, data presentation, and conclusing drawing. The results of the study it can be concluded that tradition of the heirloom carnival of Satu Sura Mangkunegaran Palace Surakarta is a sacred procession and gets blessings, because in the month of Satu Sura there are many activities of contemplain, tafakur, and self instropection to the God. The conclusion of this study is that the participation of people from various regions who follow the procession of Satu Sura Heritage Carnival at the Mangkunegaran Palace in Surakarta ignores the rules or regulations of the Mangkunegaran Palace, Surakarta. The conclusion of this research is the philosophy that we can take from this procession is to introspect, and this Kirab procession was followed by many people who were enthusiastic to see the procession. The obstacles faced during the procession moreover were the people who enthusiastic to see to make the perpetrators not concentrate.